Retrospective analysis of total direct medical costs associated with hepatitis B patients with oral antiviral versus pegylated interferon therapy in Turkey. Issue 11 (18th February 2014) - Altinbas, A.; Baser, E.; Burkan, A.; Ertugay, E.; Kariburyo, M. F.; Baser, O.
Summary To explore healthcare costs associated with antiviral treatment of hepatitis B virus (HBV) in Turkey. Research‐identified data from a claims processing system for all Turkish health insurance funds were analysed. Adult patients prescribed oral antiviral and pegylated interferon treatment were identified between 1 January 2010 and 31 December 2010. The first prescription date was defined as the index date. Patients were required to have HBV diagnosis within the 6‐month pre‐index period. Pharmacy, outpatient and inpatient claims were compiled over the study period for the selected patients, and risk‐adjusted 1‐year healthcare costs of patients with oral antiviral and pegylated interferon treatment were compared. Risk adjustment was carried out using propensity score matching, controlling for baseline demographic and clinical characteristics. A total of 9618 patients were identified, of which 9074 were treated with oral antiviral medication and 544 with pegylated interferon medication. The oral antiviral treatment group was older (45.28 vs 42.19, P < 0.001), less likely to be female (32.17% vs 39.71%, P < 0.001) and to reside in Southeastern Anatolia (8.29% vs 13.97%, P < 0.001) or Mediterranean region (8.90% vs 11.76%, P < 0.03) and had higher Elixhauser comorbidity index scores (60.22% vs 74.08%, P < 0.001) than the pegylated interferon group. After adjusting for confounding factors, total medical costs for pegylated interferon patients were €2771 higher than for oral antiviral patients (P < 0.001), due to higher outpatient and prescription costs. For annual healthcare costs for antiviral treatment options for HBV patients in Turkey, after adjusting for age, gender, region and comorbid condition differences, oral antiviral treatment is more costly than pegylated interferon treatment.